Stylistic Analysis of Maya Angelouâ€™s â€œWoman Workâ€ - Isti'anah, Arina; Krismarini, Caecilia Riris; Putri, Elisabet Ayu Pramesthi Lebdo (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This paper presented the stylistic analysis of a poem by Maya Angelou, â€œWoman Workâ€. This stylistic analysis focused on analyzing two language levels, phonology and syntax, covering the study of sound repetition, transitivity, and pronoun. The phonological features employed in the poem were assonance and consonance. On the other hand, the syntactic features were in the form of material processes that described the works of a woman. The employment of pronoun referred to the poet and nature. This analysis found that Angelou positioned nature as an essential part of a woman's life as it helped her to provide a living to her family. Further, nature was placed as an Actor that helped her face her world as a woman. This paper concludes that stylistics is applicable to analyse literary works in an objective way as it provides the hard data.Â Keywords: stylistics, poem, woman, AngelouÂ